Neighborhood Opportunity and Location Affordability for Low-Income Renter Families. Issue 4 (2nd September 2016) - Acevedo-Garcia, Dolores; McArdle, Nancy; Hardy, Erin; Dillman, Keri-Nicole; Reece, Jason; Crisan, Unda Ioana; Norris, David; Osypuk, Theresa L.
Abstract: We use the Location Affordability Index (LAI) and the newly developed Child Opportunity Index (COI) to assess, for the first time, the tradeoff between neighborhood opportunity and housing/transportation affordability facing low-income renter families in the 100 largest metropolitan areas. In addition to describing the opportunity/affordability relationship, we explore the level of balance between neighborhoods' relative cost burden and their corresponding opportunity levels to determine whether children of different racial/ethnic groups are more (or less) likely to experience cost-opportunity imbalance. Our multilevel analyses show that housing affordability is largely accounted for by the neighborhood opportunity structure within each metropolitan area. The metropolitan characteristics examined account for only a small proportion of the between-metro variance in the opportunity/affordability gradient for housing, presumably because the neighborhood opportunity structure already reflects metro area factors such as fragmentation and segregation. On the other hand, transportation affordability shows a weaker association with neighborhood opportunity. The COI/LAI association is much weaker for transportation than for housing, and a large part of the variation in the transportation gradient occurs at the metropolitan area level, not the neighborhood level. Sprawl is particularly associated with transportation affordability, with lower sprawl areas having lower transportation-cost burden. We discuss the implications of the empirical findings for defining affordability in housing assistance programs. We recommend that housing policy for low-income renter families adopt an expanded notion of affordability (housing, transportation, and opportunity) and explicitly consider equity (e.g. cost-opportunity imbalance) in the implementation of this expanded affordability definition.